Task allocation in periodontal treatment among older adults in public oral health services in Helsinki, Finland, from 2007 to 2016. - Kokkonen, Antti; Hiltunen, Kaija; Vehkalahti, Miira M.; Mäntylä, Päivi (European Journal of Oral Sciences, 2026)
The demand for non‐surgical periodontal treatment (NSPT) is increasing due to longer life expectancy and reduced edentulism. This descriptive study examined quantitatively the task allocation between dentists and dental hygienists and the influence of patient age on NSPT provision using aggregated data from electronic patient records of patients aged 60+ attending public oral healthcare in Helsinki, Finland, in the period 2007–2016. Nearly 50% of the patients received NSPT, either time‐based or complex treatments. Of all appointments, 7% involved time‐based NSPT by dentists and 13% by dental hygienists. NSPT comprised 98% of all periodontal procedures, with dental hygienists performing 60%. Dentists mainly provided short (<20 min) and ≥20 min treatments, each accounting for 8%–13% per age group, whereas longer and complex treatments were rare (1%–4%) and declined with age group. Dental hygienists increasingly performed ≥20 min treatments in the older age groups (12%–22%), with ≥30 min treatments being most common (32%–37%). Although ≥45 min procedures were infrequent, dental hygienists performed them twice as often as dentists, with a decreasing trend in the older patient groups. No obvious differences were found across study years. Findings emphasize dental hygienists' central role in periodontal care and suggest age‐related differences in treatment duration and provider allocation.